Pierwsze odkrycie grobu rowkowego z okresu wędrówek ludów w Wielkopolsce (Konarzewo, pow. Poznań ziemski, stan. 5) - Makiewicz, Tadeusz; Kaczor, Wojciech (Folia Praehistorica Posnaniensia, 2018)
The article presents a discovery of the first grooved burial, rectangular in section, from the Great Poland. It is an urn burial with multiple interments; two urns with remains of three individuals are associated with a groove. Four clusters of cremated bones composed of remains of five individuals were placed directly above. Depending upon chosen interpretation, it was a burial of three or eight individuals. The burial has been dated back to the second half of the 5th century AD. It is a manifestation of transformations in the domain of burial rites in the last phase of the Przeworsk culture. They resulted in increasingly atypical and archaeologically indefinable forms of the burial rite. The burial was placed in the west edge of the settlement composed of hall houses made of a post construction, which was founded in the years 340-352 AD. A well cemetery with cremation burials was also discovered at this site. This was a settlement complex composed of a large settlement and at least two cremation cemeteries. It is the first complex of this type in the Przeworsk culture.